Beta-Glucan, immune function, and upper respiratory tract infections in athletes - Nieman, D. C.; Henson, D. A.; McMahon, M.; Wrieden, J. L.; Davis, J. M.; Murphy, E. A.; Gross, S. J.; McAnulty, L. S.; Dumke, C. L. (Medicine & Science in Sports & Exercise, 2008)
Purpose: This study investigated the effects of oat Beta-Glucan (BG) supplementation on chronic resting immunity, exercise-induced changes in immune function, and self-reported upper respiratory tract infection (URTI) incidence in human endurance athletes.